ASSESSMENT OF ADHERENCE TO TREATMENT AND FACTORS AFFECTING IT IN PATIENTS WITH STABLE ISCHEMIC HEART DISEASE DURING THERAPY WITH NICORANDIL - S. Yu. Martsevich; Yu. V. Lukina; N. P. Kutishenko; A. V. Akimova; V. P. Voronina; O. V. Lerman; O. V. Gaisenok; T. A. Gomova; A. V. Ezhov; A. D. Kuimov; R. A. Libis; G. V. Matyushin; et al. (Рациональная фармакотерапия в кардиологии)
Working Group of the NIKEA Program. Ekaterinburg: Akulina E.N.; Izhevsk: Shinkareva S. E., Grebnev S.A.; Krasnodar: Kudryashov E.A., Fendrikova A.V.; Krasnoyarsk: Nemik D.B., Pitaev R.R., Altaev V.D., Samokhvalov E.V., Stolbikov Y.Y.; Moscow: Dmitrieva N.A., Zagrebelnyy A.D., Zakharova A.V., Balashov I.S., Leonov A.S., Sladkova T.A., Zelenova T.I., Shestakova G.N., Kolganova E.V., Maksimova M.A.; Novosibirsk: Moskalenko I.V., Shurkevich A.A.; Omsk: Loginova E.N., Gudilin V.A.; Orel: Zhuravleva L.L., Lobanova G.N., Luneva M.M.; Orenburg: Kondratenko V.Y.; Rostov-on-Don: Kalacheva N.M., Kolomatskaia O.E., Dubishcheva N.F., Romadina G.V., Chugunova I.B., Skarzhinskaia N.S.; Ryazan: Bulanov A.V., Trofimova Y.M., Nikolaeva A.S.; St. Petersburg: Savinova E.B., Ievskaia E.V., Vasileva L.B.; Tula: Zubareva L.A., Berberfish L.D., Gorina G.I., Nadezhkina K.N., Iunusova K.N., Nikitina V.F., Dabizha V.G., Renko I.E., Soin I.A.Aim. To study the adherence to treatment and the factors that affect it in patients with stable coronary heart disease during the treatment with nicorandil. Material and methods. The use of nicorandil in addition to standard antianginal therapy was recommended to patients (n=590) in a prospective, observational, multicenter NIKEA study. Patients completed original questionnaires on adherence, including a Morisky-Green test at the enroll visit. The questionnaires were filled by 423 patients (73% response). The factors that influence adherence were studied.Results. All patients were divided into 3 groups, depending on the adherence to the use of nicorandil: immediately refused to take the drug (n=150; group 1); started, but stopped taking nicorandil in the first 3 months of observation (n=75; group 2); who took nicorandil for 3 months (n=327; group 3). Potentially adherents (intention to treat) were 582 out of 590 (98.6%) patients, and actually adherents – only 327 of 552 (59.2%) patients. The main reason for non-adherence to the beginning of therapy is polypharmacy; to the continuation of the treatment that had just started – adverse events; for termination of long-term therapy – polypharmacy, adverse events and insufficient effectiveness of treatment. Group 3 had initially more severe angina pectoris: more number of angina attacks (p=0.014) and the need of short-acting nitrates (p<0.0001). Patients of the group 1 compared to the patients of group 3 did not visit the doctors more often or attended them only when necessary, violated the medical prescriptions for taking medications (p<0.05). According to the results of the Morisky-Green test, 150 patients (36.2%) were not are committed to medical recommendations, 264 (63.8%) – are committed. Women were more adherent than men (p=0.47); patients with class I angina were more adherent than patients with class III angina (p=0.027), and patients who regularly attended the treating physician (more often than once a month) were more committed to medical recommendations than patients, not visiting the treating physician (p=0.004).Сonclusion. The levels of overall adherence according to Morisky-Green test, the potential adherence according to the survey and the actual adherence of patients to treatment vary considerably. The leading cause of non-adherence at the beginning of therapy is polypharmacy, for the continuation of the recently started treatment – the adverse events; for long-term sustained treatment – equally polypharmacy, drug adverse events and the lack of treatment efficacy.